An implementation of a pedobarograph using a piezoelectric transducer array with a parallel port interface - Abundo, Michael Lochinvar S. (2004)
A pedobarograph is device that measures and displays the foot-pressure distribution over time. It is used for pre- and post-surgical medical evaluation and orthopedic appliance design. The developed pedobarograph has three main units: (1) a signal conditioning unit, (2) a data acquisition unit and (3) the display and control unit. The first unit is composed of an array of piezoelectric transducers, to convert foot-pressure to its proportional voltage, and a multiplexer board. The second unit involves a counter circuit, which provide control signals to the multiplexer, and an analog-to-digital converter interfaced to a PC's parallel port. The display unit, the monitor, displays both a 2D and 3D plot of the state of the transducer array. A program, developed using Visual Basic.NET, coordinates the operation of all these units.